Are commitment and job satisfaction affect attitude of employees towards change initiatives? - Megersa Wedajo Motuma; Belay Chekole Amaha (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
This study aimed at examining the influence of organizational commitment and job satisfaction on attitudes of employees toward change initiatives in selected public universities in Ethiopia. Self-Administered questionnaires were prepared and distributed to 200 randomly selected teachers in selected universities via e-mail addresses. By using the average score of three scales, correlation and regression analysis was made to see the relationship and influences of commitment and job satisfaction. The findings revealed that employees` general attitude towards change initiatives is influenced by Job satisfaction (p<0.05). However, it did not indicate the significant influence of employees` commitment to the attitude of employees regarding change initiatives (p>0.05). These imply that job satisfaction may play a greater role in shaping the attitude of employees to change initiatives than organizational commitment. From the results, we recommend that leaders focus on things that can enhance job satisfaction during the implementation of change initiatives